The Next 100 Years : A Forecast for The 21st Century - Friedman, George (GHQ, Rawalpindi Services Book Club, 2013)
In this book, George Friedman, founder of STRATFOR - the preeminent private intelligence and forecasting firm - focuses on what he knows best, the future. Positing that civilization is at the dawn of a new era, he offers a lucid, highly readable forecast of the changes we can expect around the world during the twenty-first century all based on his own thorough analysis and research. For example, The U.S.-Jihadist war will be replaced by a new cold war with Russia; China's role as a world power will diminish; Mexico will become an important force on the geopolitical stage; and new technologies and cultural trends will radically alter the way we live (and fight wars). Riveting reading from first to last, The Next 100 Years is a fascinating exploration of what the future holds for all of us.
Includes Illustrations, Map and Epilogue.
Keywords: International Relations -- History -- 21st Century -- International Relations--Forecasting